Healthcare after ebola. Issue 5 (May 2016) - Hands, Christopher
Abstract: In 2014 and 2015, Sierra Leone, along with its neighbours, Guinea and Liberia, experienced by far the biggest epidemic of ebola virus disease ever recorded. As the rapid spread of the virus became clear, a huge relief effort was undertaken and supported by governments around the globe. That the ebola virus was transmitted so freely and quickly in West Africa was due, in part, to the weakness of the healthcare systems in the countries which suffered the epidemic. The damage caused by ebola further undermined those systems. In the months following the end of the outbreak, the difficult work of building adequate healthcare systems for the people of Sierra Leone, Guinea, and Liberia, has begun. This article gives a personal account of the longer-term effects of the ebola epidemic on the healthcare systems in Sierra Leone.